2002
DOI: 10.4049/jimmunol.169.6.2851
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase Signaling in Activated T Cells Abrogates TRAIL-Induced Apoptosis Upstream of the Mitochondrial Amplification Loop and Caspase-8

Abstract: Fas ligand and TNF-related apoptosis-inducing ligand (TRAIL) induce apoptosis in many different cell types. Jurkat T cells die rapidly by apoptosis after treatment with either ligand. We have previously shown that mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) can act as a negative regulator of apoptosis mediated by the Fas receptor. In this study we examined whether MAPK/ERK can also act as a negative regulator of apoptosis induced by TRAIL. Activated Jurkat T cells were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 58 publications
4
64
0
Order By: Relevance
“…[14][15][16][17][18] Accordingly, it is well known that MAPK activates genes implicated in cell survival. 19 To determine whether inhibition of TRAIL-induced apoptosis exerted by PKC activation is due to the novo synthesis of survival genes, MCF-7 cells were treated with TRAIL and PKC activator phorbol-12,13-dibutyrate (PDBu) in the presence or absence of the protein synthesis inhibitor cycloheximide (CHX) (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17][18] Accordingly, it is well known that MAPK activates genes implicated in cell survival. 19 To determine whether inhibition of TRAIL-induced apoptosis exerted by PKC activation is due to the novo synthesis of survival genes, MCF-7 cells were treated with TRAIL and PKC activator phorbol-12,13-dibutyrate (PDBu) in the presence or absence of the protein synthesis inhibitor cycloheximide (CHX) (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16]35 In contrast, in melanoma and breast cancer cell lines signaling through the MAPK/Erk pathway inhibits TRAIL-induced translocation of Bax from the cytosol to mitochondria thus preventing the release of apoptogenic factors from this organelle. 17,18 In the present report, we have demonstrated that in MCF-7 breast cancer cells TRAIL and TNF-a-induced cleavage of Bid was unaffected by PKC activation and identified the mitochondrial localization of tBid as a novel target of MAPK mediated apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that MEK/ERK signaling suppresses Fasmediated apoptosis in activated T cells by inhibiting DISC-mediated activation of caspase 8. (Holmstrom et al, 2000;Tran et al, 2001;He et al, 2002;Soderstrom et al, 2002). Other antiapoptotic proteins such as Bcl-2 and BAD are regulated by activated MAPK and may contribute to survival in these NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of sphingosine and S1P in cell pellets were determined by HPLC following a previously described procedure with modification (33). Cell pellets were lysed with 0.2 N NaOH for the determination of protein content.…”
Section: Measurement Of Sphingosine and S1pmentioning
confidence: 99%